Christianity's Russian Temptation. - Ahmari, Sohrab (America Magazine: The Jesuit Review of Faith & Culture, 2017)
The article discusses the alleged threat of de-Christianization in Russia and its president Vladimir Putin's views on preserving the faith, traditional family and country against liberalism. It discusses the skepticism surrounding Putin's views on protecting Christianity due to his reportedly corrupt and aggressive policies, his war on religious liberty. It talks about Russian Orthodox Church's supremacy due to Putin's patronage and religion under his allegedly imperialistic outlook.